The Effectiveness of Android Smartphone-Based Mobile Applications in Learning English Grammar - Matius Tandikombong; Judith Ratu Tandi Arrang; Yusem Baru (Jurnal Sinestesia, 2023)
This study is quantitative research. The purpose of this study is to determine the effectiveness of using Android smartphone-based mobile applications to learn English grammar. The population of this study was the first-year students in the English language education study program. To determine the research sample, the writers used the cluster sampling technique. The sample for this research was 20 students. The results of this study, after analyzing the obtained data, show that the Android smartphone-based mobile apps application is effectively used in learning English grammar. The study revealed that the post-test was higher than the pre-test, with the post-test scoring 87.04 and the pre-test scoring 42.65. The significance results also indicate that the t-test is greater than the T-table score, with t-test = 11.350 and t-table = 2.093, respectively.